Preoperative Music Listening in Pelvic Reconstructive Surgery: A Randomized Trial. Issue 8 (12th August 2021) - Chen, Yufan Brandon; Barnes, Hayley; Westbay, Lauren; Wolff, Birte; Shannon, Megan; Adams, William; Acevedo-Alvarez, Marian; Mueller, Elizabeth R.; Pham, Thythy T.
Abstract : Objectives: We aimed to investigate the effect of music listening on preoperative anxiety compared with usual care in patients undergoing pelvic reconstructive surgery. Methods: Patients scheduled for pelvic reconstructive surgery were enrolled on the day of surgery. Participants were randomized to either the usual care (control group) or to music listening on headphones (music group) before their surgery. Participants completed the Spielberg State-Trait Anxiety Inventory form Y1 to measure baseline state anxiety levels before surgery and again after 30 minutes of usual care or music listening. The primary outcome was the change in state anxiety score as measured by the State-Trait Anxiety Inventory form Y1. Results: Sixty-nine women completed the study (35 assigned to the control group and 34 assigned to the music group). Analysis of the primary outcome included 66 participants (34 in the control group and 32 in the music group). Improvement in state anxiety was significantly better for patients assigned to music listening (−6.69; SD, 6.98) than for patients assigned to the control group (−1.32; SD, 8.03; P = 0.01). Six weeks postoperatively, patients in the music group (n = 29) reported higher overall satisfaction when compared with those in the control group (n = 31, P = 0.03). Conclusion: Patients undergoing pelvic reconstructive surgery present with moderate anxiety on the day of surgery. Allowing patients to listen to their preferred music is a simple intervention that may lower preoperative anxiety and improve satisfaction in this patient population.